"Heritage on Exile": Reflecting on the Roles and Responsibilities of Heritage Organizations towards Those Affected by Forced Migration. (15th September 2016) - Schofield, John
Abstract : This short contribution is a simple reflection on the current refugee crisis, grounded in an active interest in the contributions heritage organisations can or should make towards ameliorating life-changing impacts on people directly affected by situations beyond their control. It also reflects on a career working within the UK heritage sector that can appear to me sometimes rather detached from contemporary life, or slow to respond to it. While recognising the importance of heritage in post-war reconstruction, this paper concerns the people themselves, forced to escape conflict and seek safe haven elsewhere at the moment of crisis, when they are at their most vulnerable, disorientated, traumatised and isolated. They, it seems to me, are the immediate concern. Post-war reconstruction (or debates about whether this is appropriate) can follow later.